Organizational Communication Model on the Implementation of the Sakinah ‘Aisyiyah Family’ Sumatera Utara - Kholil, Syukur; Nasution, Hasyimsyah; Amini, Nur Rahmah (Budapest International Research and Critics University, 2021)
The purpose of this study was to find about Organizational Communication Model on the Implementation of the Sakinah 'Aisyiyah Family. This study used qualitatif research. The result in this show that the leadership and members of 'Aisyiyah in North Sumatra are already familiar with the concept of the sakinah family. However, not all members and leaders know in detail the material of the sakinah family according to the book of the central leadership 'Aisyiyah. The observation made by the author is that someone has been selling guidance books for the sakinah family from the central leadership of 'Aisyiyah at the regional leadership office of North Sumatra. For out-of-region bookings, you can contact the relevant contact or ask the regional leadership management.